An Open Trial to Test Participant Satisfaction With and Feasibility of a Computerized Intervention for Women Veterans With Sexual Trauma Histories Seeking Primary Care Treatment - Creech, Suzannah K. (Violence against women, 2021)
Sexual trauma is prevalent among women veterans and associated with health risks including hazardous drinking, intimate partner violence (IPV), and post-traumatic stress disorder (PTSD). Safe and Healthy Experiences (SHE) is a computerized intervention to reduce these health risks. SHE was pilot tested in an open trial (N = 20) with women veterans with a history of sexual trauma and associated health risks. Women reported high satisfaction with the intervention and computerized delivery and they evidenced reductions in hazardous drinking, IPV, and PTSD at 4 months. SHE appears to be satisfactory, feasible, and potentially beneficial to women veterans.